Student Behavior and Its Association with Multi-Device Addiction and Back Pain in Western Romania - Brigitte Osser; Csongor Toth; Gyongyi Osser; Carmen Delia Nistor-Cseppento; Victor Niculescu; Laura Ioana Bondar (Balneo and PRM Research Journal)
The rapid development of modern technologies has brought enormous benefits to today's society in all areas of life. On the one hand, they have a positive effect on people's relationships, learning, and development. On the other hand, the incorrect use of electronic devices can cause health damage and serious problems. In recent years, the use of digital devices has increased among students, highlighting the problem of digital addiction. This study aimed to observe the problems of spinal pain associated with the use of mobile phones by students in schools and to find constructive solutions to turn mobile phones into an effective learning tool to be used only in the classroom. The method used in this study was to apply questionnaires to a sample of 506 students from Arad County. The results of this study showed that students in the study group are addicted to the internet and social networks, and also confirmed that some of them cannot experience all this without sacrificing their physical and mental health. In conclusion, educational and policy measures to combat digital addiction are urgently needed worldwide. Schools should implement comprehensive digital literacy programs to educate students about the risks of excessive use of digital devices and promote healthy online behaviors.